KAJIAN GENDER DALAM PERSPEKTIF PERSYARIKATAN MUHAMMADIYAH DI KABUPATEN SIKKA - Sunardin Sunardin; Nur Chotimah; Gisela Nuwa (Jurnal Studi Gender dan Anak, 2023)
This study aims to examine gender equality from the perspective of the Muhammadiyah organization on Muhammadiyah business charity in Sikka Regency and how the efforts of the Muhammadiyah Regional Leadership (PDM) Sikka in upholding gender justice in Muhammadiyah business charity in Sikka Regency. This research method uses a qualitative approach. Data collection techniques are through three steps, namely observation, in-depth interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion/verification. The results of the research show that gender equality is applied in the perspective of Muhammadiyah on Muhammadiyah business charity in the Sikka Regency, namely being given freedom, and being counted, Muhammadiyah women already exist in Muhammadiyah charity businesses, and women are at the forefront. Meanwhile, PDM Sikka's efforts in upholding gender justice are following the Tarjih decision accompanied by endeavor and patience, and socialization. Keywords: Gender Justice, Business Charity, Organization